Molecular monitoring of microbial diversity in an UASB reactor - Casserly, Carolina (2003)
The dynamics of the microbial community structure of a full-scale upflow anaerobic sludge blanket reactor has been analyzed using culture-independent 16S rRNA-based methods. During the start-up of the process, denaturing gradient gel electrophoresis of bacterial rDNA showed significant changes in the structure of the bacterial community, but only a slight increase in the bacterial diversity. Associated with the shifts in bacterial populations, significant changes in the relative abundance of different methanogenic species are revealed by taxon-specific dot-blot experiments. The ratio of archaeal 16S rRNA to bacterial 16S rRNA, but none of the individual microbial taxons, correlated with the maximum allowable daily organic loading rate. The results argue against the notion that many anaerobic wastewater treatment systems fail due to the lack of adequate inoculum.